2016
DOI: 10.1097/pai.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of CD105 and TGF-β1 in Oral Squamous Cell Carcinoma and Adjacent Apparently Normal Oral Mucosa and its Correlation With Clinicopathologic Features

Abstract: Angiogenesis in oral squamous cell carcinomas (OSCC) is essential for its growth, invasion, and metastasis. This entails a shift in the balance between proangiogenic and antiangiogenic factors. CD105 and TGF-β1 are 2 such proangiogenic factors wherein CD105 exerts its angiogenic effect by binding to and modulating the TGF-β1 pathway. A total of 50 resected specimens of OSCC were considered. One tissue specimen was taken from tumor proper and another specimen from adjacent apparently normal mucosa (AANM). Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…A similar result was described by Martone et al, who found that the density of neoformed microvessels (CD105 + ) was significantly higher in groups with T3/T4 tumors and those with an advanced clinical stage. Nair et al also demonstrated a significant increase in number of CD105 + microvessels as the T stage increased; the group further found increases in the density of neoformed microvessels in OSCC as compared with negative controls. Thus, increased expression of CD105 is evidently directly associated with disease progression, which reveals that this parameter may also be an indicator of oral cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…A similar result was described by Martone et al, who found that the density of neoformed microvessels (CD105 + ) was significantly higher in groups with T3/T4 tumors and those with an advanced clinical stage. Nair et al also demonstrated a significant increase in number of CD105 + microvessels as the T stage increased; the group further found increases in the density of neoformed microvessels in OSCC as compared with negative controls. Thus, increased expression of CD105 is evidently directly associated with disease progression, which reveals that this parameter may also be an indicator of oral cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 90%
“…The inflammatory markers TAN, MMP‐9, and IL‐17 have been individually proposed as prognostic biomarkers in oral squamous cell carcinoma (OSCC) . Garley et al and Li et al observed that the supernatants and blood serum of patients with oral cancer exhibit higher concentrations of IL‐17 than those of healthy subjects, and this difference is associated with tumor growth and metastasis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD105 is a transmembrane glycoprotein expressed primarily in ECs and tumor cells (15,16). Tumoral CD105 has been defined as a novel independent prognostic marker, whereas the microvessel density labelled by the endothelial marker CD105 (MVD-CD105) negatively correlates with tumor development of human hepatocellular carcinoma (HCC) and renal cell carcinoma (13,17).…”
Section: Introductionmentioning
confidence: 99%